The impact of the economic disruption caused by the Covid-19 pandemic on the liquidity of enterprises - Kuciński, Andrzej (Journal of Finance and Financial Law, 2025)
The purpose of the article. The purpose of the article is to analyze the impact of rapid changes in the economic environment caused by the Covid-19 pandemic on the level of liquidity. The analysis will be carried out in broad terms, i.e. for non-financial companies in Poland, and in narrower terms, i.e. for non-financial companies in the section of wholesale and retail trade; repair of motor vehicles, including motorcycles, as well as for companies representing the clothing and footwear sector on the Warsaw Stock Exchange (WIG-clothing). The article verifies the research hypothesis stating whether non-financial companies in Poland, as well as non-financial companies from the wholesale and retail trade section and companies from the clothing and footwear sector listed on the Warsaw Stock Exchange (WIG-clothing), have experienced deterioration in liquidity. Methodology. The analysis and evaluation of the impact of the disruption in the economy caused by the Covid-19 pandemic on the liquidity of enterprises was carried out on the basis of selected statistics – financial indicators for non-financial enterprises with books of accounts, where the number of employees was 50 or more in general and for the section of wholesale and retail trade; repair of motor vehicles, including motorcycles and companies from the WIG- clothes index listed on the Warsaw Stock Exchange. The study used as research methods: a review of the literature on the subject, an analysis of selected statistical data from the Central Statistical Office, an analysis of selected financial indicators used in assessing the financial condition of enterprises, and deductive reasoning in formulating the conclusions from the research results obtained. The analysis was conducted for the years 2018–2023 using financial data from the Notoria Serwis database and statistical data from the Central Statistical Office – Local Data Bank. Results of the research. The results of the study show that the Covid-19 pandemic did not cause any negative effects on financial liquidity in the surveyed group of non-financial enterprises employing 50 people or more, nor in enterprises included in section G in the economy and in the group of companies in the WIG-clothes index listed on the Warsaw Stock Exchange.